Parte de um jogo digital para desenvolver o pensamento computacional : o TCC integrado a um projeto de doutorado em educação. - Reis, Pedro Sturaro dos (2024)
Computational thinking is one of the essential skills in the current era of knowledge, and must be developed since basic education. The use of games in education is a strategy that has been used with the purpose of engaging students, making the learning process ludic and thus more effective. This course completion work, which is linked to a PhD research in the Postgraduate Program in Education at this University, aims to produce a digital game that enables high school students to develop the four pillars of computational thinking. For this, a script was created with the “pirate” theme and respective challenges. Solving the challenges requires the adoption of one or more pillars of computational thinking. The pixel art style was chosen for the visual design, both because of the facility for drawing characters, objects and scenes, and the little requirements of hardware to execute it. In total, thirteen challenges were planned, but only three were implemented, due to lack of time. To finalize the implementation and carry out the testing stages, an external research project is underway within the Computing Department of the Federal University of Sergipe, with two more student researchers.